Candidosis in Guinea Fowl (Numida meleagris) - Dias Carneiro, Heitor; Dias, Thomas; Fialho, Daniele Soares; Rocha, Elisabeth; Dias, Mariana; Costa, Carlos Henrique; Pereira, Virginia; Abreu, Dayse (Acta Scientiae Veterinariae, 2024)
Background: Candidosis is a fungal disease caused by yeast of the genus Candida, which affects various bird species. The most common infection method involves ingesting contaminated food or water; however, contaminated environments, such as the litter and facilities may also expose birds to Candida spp. Diagnosis relies on lesion observation, direct microscopic examination, or mycological culture for isolation and identification. This report details an outbreak of candidosis in Guinea fowl, confirmed by etiological diagnosis, including isolation, identification, and anatomopathological analysis. Cases: Birds housed in an intensive Guinea fowl farm exhibited clinical signs in the 2nd week of life. Mortality increased in the 3 rd week after the transfer from the rearing area to the ground area, with daily deaths reaching 30-40 birds. The affected birds displayed prostration, emaciation, diarrhea, and ruffled feathers. Tilmicosin-based antibiotic treatment was administered early in life and no response was observed after treatment with antifungal gentian violet. Five 7-week-old Guinea fowl from the farm underwent necropsy to observe macroscopic lesions and collect samples from the esophagus, crop, proventriculus, and intestines for mycological culturing and histopathological analysis using standard techniques. Macroscopic examination revealed alterations such as whitish, circular, and ulcerative lesions in the palate, esophagus, crop, and proventriculus; dilated and empty crops with thickened mucosa; accumulated urate in the ureters; and variations in intestinal mucosal thickness from thickened to thin. Histopathological analysis identified superficial layers of the esophagus, crop, and proventricular mucosa colonized with numerous yeast-like forms and pseudohyphae, characteristic of Candida spp. Esophagus and crop samples were cultured on YEPD agar and growth was verified under a stereoscopic microscope for culture purity. Ten colonies were isolated from these cultures, inoculated into YEPD broth tubes, and then incubated at 25°C for 48 h. Microcultures of the isolates on glass slides with 10 x 10 mm YEPD agar fragments were prepared and incubated at 25°C for 5-10 days in a humid chamber. After incubation, lactophenol cotton blue staining was performed, followed by microscopic observation of cellular morphology. The germ tube test was also performed by inoculating theisolates into tubes with 0.5 mL of human serum, incubating them at 37°C for 2 h, and then examining them under an optical microscope. The yeast isolates were tested on CHROMagar® Candida medium for chromogenic behavior, incubated at 30°C for 48 h, and the coloration observed was consistent with Candida albicans. Discussion: The observed anatomopathological lesions were consistent with those described in other cases of candidosis. The combination of antimicrobial use and digestive tract lesions supported the presumptive diagnosis of the disease, with a definitive etiological diagnosis confirmed by the mycological culture results. Treatment with gentian violet in water and nystatin in feed failed to yield the expected results. Administering antibiotics early in a bird’s life can disrupt the balance of digestive tract microbiota, leading to yeast colonization. All subsequent flocks were treated with probiotics using the competitive exclusion principle to inhibit pathogenic bacterial microbiota growth and maintain a balanced commensal microbiota. Keywords: Guinea fowl, candidiasis, fungal infection, mycose, microbiota, probiotics. Título: Candidose em galinhas d’Angola (Numida meleagris) Descritores: galinha d’Angola, candidíase, infecção fúngica, micose, microbiota, probióticos.